Pregled izvajanja mednarodne zakonodaje o ohranjanju morske biotske raznovrstnosti v Sloveniji - Centrih, Tina (Varstvo narave, 2015)
The article discusses the state of affairs concerning the implementation of international, European and national legal mechanisms guiding Slovenia at its attempts to attain favourable conservation status of marine biodiversity. One of these mechanisms is the commitment to stipulate adequate safety measures on at least 10% of the sea and its coast, including marine protected areas. A review of the available data shows that the implementation of provisions stipulated by various international conventions and European legal order is not always consistent. Quite alarming is the fact that certain rare and endangered species and characteristic habitat types in the Slovenian Sea are still without designated protection areas. The situation concerning the existing marine protected areas' management is also unsatisfactory, given that only one out of three such areas is managed at the moment. Upon the analysis of the current situation we believe that a concrete, temporally defined action plan should be adopted for a more effective biodiversity protection of the Slovenian Sea, with which implementation of the measures for the fulfilment of adopted targets concerning the preservation of marine biodiversity would be provided. To conclude we propose a list of measures that would serve as a framework for the mentioned action plan. This way the article can serve as a guideline as to understand what our focus should be in the future in order to achieve a good conservation status of the Slovenian marine environment and its biodiversity. At the same time this measures could allow for the fulfilment of requirements demanded from Slovenia by international conventions and European legislation.
Keywords: Barcelonska konvencija; biodiversity; biotska raznovrstnost; Konvencija o biotski raznovrstnosti; morje; Morska direktiva; morska zavarovana območja; Natura 2000; sea; Slovenia; Slovenija